Myelin-associated glycoprotein modulates apoptosis of motoneurons during early postnatal development via NgR/p75 NTR receptor-mediated activation of RhoA signaling pathways - Palandri, Anabela (2015)
Myelin-associated glycoprotein (MAG) is a minor constituent of nervous system myelin, selectively expressed on the periaxonal myelin wrap. By engaging multiple axonal receptors, including Nogo-receptors (NgRs), MAG exerts a nurturing and protective effect the axons it ensheaths. Pharmacological activation of NgRs has a modulatory role on p75 NTR -dependent postnatal apoptosis of motoneurons (MNs). However, it is not clear whether this reflects a physiological role of NgRs in MN development. NgRs are part of a multimeric receptor complex, which includes p75 NTR, Lingo-1 and gangliosides. Upon ligand binding, this multimeric complex activates RhoA/ROCK signaling in a p75 NTR -dependent manner. The aim of this study was to analyze a possible modulatory role of MAG on MN apoptosis during postnatal development. A time course study showed that Mag-null mice suffer a loss of MNs during the first postnatal week. Also, these mice exhibited increased susceptibility in an animal model of p75 NTR -dependent MN apoptosis induced by nerve-crush injury, which was prevented by treatment with a soluble form of MAG (MAG-Fc). The protective role of MAG was confirmed in in vitro models of p75 NTR -dependent MN apoptosis using the MN1 cell line and primary cultures. Lentiviral expression of shRNA sequences targeting NgRs on these cells abolished protection by MAG-Fc. Analysis of RhoA activity using a FRET-based RhoA biosensor showed that MAG-Fc activates RhoA. Pharmacological inhibition of p75 NTR /RhoA/ROCK pathway, or overexpression of a p75 NTR mutant unable to activate RhoA, completely blocked MAG-Fc protection against apoptosis. The role of RhoA/ROCK signaling was further confirmed in the nerve-crush model, where pretreatment with ROCK inhibitor Y-27632 blocked the pro-survival effect of MAG-Fc. These findings identify a new protective role of MAG as a modulator of apoptosis of MNs during postnatal development by a mechanism involving the p75 NTR /RhoA/ROCK signaling pathway. Also, our results highlight the relevance of the nurture/protective effects of myelin on neurons.